Investigation of the lethal and behavioral effects of commercial insecticides on the parasitoid wasp Copidosoma truncatellum. (January 2018) - Ramos, Rodrigo S.; de Araújo, Vitor C.R.; Pereira, Renata R.; Martins, Júlio C.; Queiroz, Obiratanea S.; Silva, Ricardo S.; Picanço, Marcelo C.
Abstract: Copidosoma truncatellum (Hymenoptera: Encyrtidae) is an important parasitoid wasp of the soybean looper, Chrysodeixis includens, but its effectiveness can be severely curtailed by the application of certain insecticides. Therefore, to identify insecticides that are potentially compatible with C. truncatellum, the lethal and behavioral effects of nine chemicals used to control the soybean looper were evaluated for their toxicity to the wasp. Chlorantraniliprole, chlorfenapyr, flubendiamide, and indoxacarb were the least toxic insecticides to the parasitoid, resulting in mortalities of less than 25%. In contrast, cartap, deltamethrin, and methomyl caused 100% mortality, and acephate and spinosad caused 76% and 78% mortality, respectively. At least one of the detoxifying enzymes (monooxygenase, glutathione S-transferase, and/or esterases) may be involved in the mechanisms underlying the selectivity of chlorantraniliprole, chlorfenapyr, flubendiamide, and indoxacarb for the parasitoid based on the results for the insecticide plus synergist treatment. Changes in the behavioral patterns (walking time and resting time) of the parasitoid were found with exposure to acephate, flubendiamide, indoxacarb and methomyl, but behavioral avoidance was not observed. Our results indicate that the insecticides chlorantraniliprole and chlorfenapyr are the most suitable for inclusion in integrated pest management strategies for the control of C. includens . Highlights: The effects of nine insecticides on the parasitoid C. truncatellum were evaluated. Chlorantraniliprole, chlorfenapyr, flubendiamide and indoxacarb showed the lowest toxicities to the parasitoid. Cartap, deltamethrin and methomyl caused 100% parasitoid mortality. Acephate, flubendiamide, indoxacarb and methomyl changed the behavior of the parasitoid. Chlorantraniliprole and chlorfenapyr are the most suitable insecticides for IPM programs.